Educação em segurança alimentar: como e porque higienizar as mãos - Antonio, Karina Jesus [UNESP]; Cruz, Rosiane Ceciliano [UNESP]; Levcovitz, Isabela Lopes da Silva [UNESP]; Santos, Pricila Veiga dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work was developed within the Extension Project "Science Delicious" of the Faculty of Agricultural Sciences of UNESP in Botucatu and aimed to develop a didactic-pedagogic material on topics related to food safety education to submit investigative and play activities to facilitate learning by students from both the elementary school, as of early childhood education. An investigative activity was performed developing a culture media based on commercial gelatin, to investigate microbial growth comparing both washed and dirty hands. A music parody "Mamãe eu quero" was developed containing the step by step of how to wash hands properly was composed. They were also produced explanatory texts in simplified language for teacher information that can also be used with students, and power point slides, with step by step of how to wash their hands properly. This material was tested in children of the fifth grade of elementary school, and children from kindergarten between 4 and 5 years. The illustrations and comments from students and teachers involved were very positive and indicated that material was efficient in producing significance for students, learning not in a memoristic way.

Este trabalho foi desenvolvido dentro do Projeto de Extensão “Ciência Deliciosa” da Faculdade de Ciências Agronômicas da UNESP de Botucatu e teve como objetivo desenvolver um material didáticopedagógico sobre tópicos ligados ao Ensino de Segurança Alimentar que apresentasse atividades investigativas e lúdicas para facilitar a aprendizagem por alunos tanto do Ensino Fundamental, quanto da Educação Infantil. Foi desenvolvida uma atividade investigativa de produção de meios de cultura a partir de gelatina, onde o aluno participa desde a confecção dos meios de cultura até a avaliação do crescimento microbiano. Foi elaborada uma paródia da música “mamãe eu quero” cantando o passo a passo de como lavar as mãos de forma correta. Foram ainda produzidos textos explicativos em linguagem simplificada para informação do professor, podendo também ser utilizado com os alunos e slides em power point, com o passo a passo de como lavar as mão de forma correta. O presente material foi testado em crianças do quinto ano do Ensino Fundamental, e com crianças da Educação Infantil entre 4 e 5 anos. As ilustrações e comentários dos alunos e professores envolvidos Foram bastante positivos e indicaram que o material foi eficiente em resultar em significado para o aluno promovendo o aprendizado de forma não memorística.
Keywords: Food safety; Wash your hands; Education; Segurança alimentar; Lavar as mãos; Educação